2018
DOI: 10.1053/j.ajkd.2018.02.351
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing in Clinical Settings

Abstract: Genetic testing is used for screening, diagnosis, and prognosis of diseases consistent with a genetic cause and to guide drug therapy to improve drug efficacy and avoid adverse effects (pharmacogenomics). This In Practice review aims to inform about DNA-related genetic test availability, interpretation, and recommended clinical actions based on results using evidence from clinical guidelines, when available. We discuss challenges that limit the widespread use of genetic information in the clinical care setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 73 publications
0
31
1
Order By: Relevance
“…Furthermore, metabolic syndrome was seen in 15% (3/20) of patients in this research. Our study revealed an increased risk of 1.13 and odds of 1.5 for ESKD in high-risk allele group in this research but the study by Franceschini et al said individuals carrying two APOL1 risk genotype (high risk; 13% Africans Americans and 2% of U.S. Hispanics/Latinos of Caribbean background) have an increased risk for ESKD (odds ratio of ∼7) and for FSGS odds ratio of 10 to 29 including HIV nephropathy [29]. The present study showed a lower mean age of ESKD and hemodialysis onset in high vs low-risk allele group.…”
Section: оригінальні наукові роботиcontrasting
confidence: 71%
“…Furthermore, metabolic syndrome was seen in 15% (3/20) of patients in this research. Our study revealed an increased risk of 1.13 and odds of 1.5 for ESKD in high-risk allele group in this research but the study by Franceschini et al said individuals carrying two APOL1 risk genotype (high risk; 13% Africans Americans and 2% of U.S. Hispanics/Latinos of Caribbean background) have an increased risk for ESKD (odds ratio of ∼7) and for FSGS odds ratio of 10 to 29 including HIV nephropathy [29]. The present study showed a lower mean age of ESKD and hemodialysis onset in high vs low-risk allele group.…”
Section: оригінальні наукові роботиcontrasting
confidence: 71%
“…These genes include APOL1 , relevant to individuals with African ancestry, as well as other genes identified from African-American, Asian and Caucasian populations, with or without diabetes mellitus. Their clinical validity has been reviewed elsewhere [23].…”
Section: Variant Selectionmentioning
confidence: 99%
“…Pharmacogenetic (PGt) testing as a relatively new tool for the personalized treatment and prevention of chronic diseases, is a significant medical advancement. 1 While PGt studies investigate individuals' responses to medications based on single-gene mutations, pharmacogenomics (PGx) approaches imply the study of many genes or whole sets of genes. 2 Although PGt has potential to improve drug safety and efficacy, its acceptance in medical practice depends heavily on the ethical issues that need to be addressed to ensure the appropriate use of PGt testing.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although PGt has potential to improve drug safety and efficacy, its acceptance in medical practice depends heavily on the ethical issues that need to be addressed to ensure the appropriate use of PGt testing. 1 Some ethical challenges arise from the application of ethical principles that support patient autonomy and confidentiality on one hand, 3 and what genetic information can be revealed on the other hand. 4 After the successful completion of Human Genomic Project, the availability of DNA sequences has rapidly advanced the diagnosis of genetic diseases by identifying genetic markers that link inherited genetic diseases with the responsible genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation